Pengaruh Media Sosial dan Perilaku Konsumen Terhadap Keputusan Pembelian Produk Fashion Pada Generasi Z di Wilayah Mojokerto - Delmy Fergin Elmy Junti; Iswati Iswati; Anis Fitriyasari; Eny Sulistyowati (Jurnal Manajemen Bisnis Era Digital, 2024)
This study aims to analyze the influence of social media and consumer behavior on the decision to purchase fashion products. This study uses quantitative methods with questionnaire distribution techniques. Data was collected from generation Z in the Mojokerto region and obtained 86 respondents who were actively using social media to find information and buy fashion products. The results of the analysis that had been carried out using SPSS in the t test showed that social media affected the purchase decision with the results of the tcount value of 4,436> ttable 1,9886 with a significant 0,000 <0.05 and consumer behavior affected the purchase decision with the results of the tcount value of 3,667> Ttable 1,9886 with significant 0.001 <0.05. While the results in the F test show that social media and consumer behavior have a simultaneous effect on purchasing decisions with the results of the value of F count 25,981> F Table 3,9546 with a significant 0,000 <0.05 which means that social media variables and consumer behavior influence purchasing decisions. The findings of this study indicate that social media and consumer behavior are an important factor that needs to be considered by the fashion brand in developing their marketing strategies. Keywords: This study aims to analyze the influence of social media and consumer behavior on the decision to purchase fashion products. This study uses quantitative methods with questionnaire distribution techniques. Data was collected from generation Z in the Mojokerto region and obtained 86 respondents who were actively using social media to find information and buy fashion products. The results of the analysis that had been carried out using SPSS in the t test showed that social media affected the purchase decision with the results of the tcount value of 4,436> ttable 1,9886 with a significant 0,000 <0.05 and consumer behavior affected the purchase decision with the results of the tcount value of 3,667> Ttable 1,9886 with significant 0.001 <0.05. While the results in the F test show that social media and consumer behavior have a simultaneous effect on purchasing decisions with the results of the value of F count 25,981> F Table 3,9546 with a significant 0,000 <0.05 which means that social media variables and consumer behavior influence purchasing decisions. The findings of this study indicate that social media and consumer behavior are an important factor that needs to be considered by the fashion brand in developing their marketing strategies.